AB0781 Psoriatic arthritis in psoriasis patients: results of a french survey. (15th June 2017) - Claudepierre, P; Richebé, P; Benkhalifa, S; Mohand, D Sid; Charles, B; Braults, Y; Lahfa, M
Abstract : Background: Early detection of psoriatic arthritis (PsA) in patients with skin psoriasis (Pso) is critical to reduce the risk of joint damage, disability, and comorbidities. However PsA is mostly under-diagnosed in patients with Pso. Objectives: first to compare characteristics of patients with Pso without PsA with those of patients with Pso and PsA, then to compare patients with Pso and potential but undiagnosed PsA (puPsA) to the other patients. Methods: 817 patients completed an online questionnaire published by the French Psoriasis Patients Association, including multiple-choice questions regarding in particular past and current symptoms. For analysis, a first comparison was performed between patients with Pso without known PsA and patients with Pso and PsA, then between patients with symptoms suggestive of PsA (puPsA group), i.e., patients with past or current joint or back pain accompanied by waking up at night and/or morning stiffness, with PsA patients on the one hand, and with patients without known PsA and without symptoms suggestive of puPsA, on the other hand. Results: 746 patients reported having Pso of which 192 (25.7%) had also PsA. Among the 554 patients without known PsA, 190 (34.3%) had symptoms suggestive of PsA, 101 (18.2%) had rheumatologic symptoms not suggestive of PsA, and 263 (47.5%) had no rheumatologic symptoms. The comparison, in multivariate analysis, between patients with Pso and PsA and patients with Pso without known PsA showed significant differences (p<0.05): Pso and PsA patients had more often current bone or joint pain at any time (OR=7.8), joint pain during the day (OR =2.45), stiff back or joints on waking (OR=1.77), painful and swollen fingers and toes (OR=3.15), past joint pain during the day (OR=3.05), and drug in tablet form (OR=2.07), biotherapy alone (OR=5.45) or with DMARDs (OR=16.06); conversely they had less often guttate psoriasis (OR=0.54). Results of the multivariate analysis comparing patients with puPsA to the other patients are shown in Tables 1 and 2 (comparison with patients with Pso and PsA in Table 1 ; comparison with patients with Pso without known PsA in Table 2 ). Conclusions: That survey on Pso patients showed that a fourth of them also had PsA, but more importantly that about another fourth had puPsA, highlighting the underdiagnosis of PsA. It suggests that presence of fatigue and nail changes might raise suspicion of PsA in Pso patients. Disclosure of Interest: P. Claudepierre Grant/research support from: AbbVie, MSD, Roche, Pfizer, Consultant for: AbbVie, BMS, Celgene, Janssen, MSD, Novartis, Pfizer, Roche, UCB, P. Richebé: None declared, S. Benkhalifa: None declared, D. Sid Mohand: None declared, B. Charles: None declared, Y. Braults: None declared, M. Lahfa Consultant for: investigator or speaker for AbbVie, MSD, Celgene, Janssen, Novartis, Pfizer, Roche, Takeda, UCB, Lilly, Leo Pharma, Galderma, Astellas, Pierre Fabre. Dermatology.